THE ROLE OF AUTHENTICITY IN YOGYAKARTA CULINARY TOURISM - Evi Octaviani; Rr. Ratna Roostika (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
This study aims to determine the effect of authenticity on brand awareness, brand image and perceived quality. To determine the effect of brand awareness, brand image and perceived quality on Brand Loyalty. To find out the effect of brand loyalty on brand choice intention in culinary tourism in Yogyakarta. By using primary data through distributing questionnaires as many as 250 respondents, filtering up to 220 data that are suitable for processing, this research data is then processed using the Structural Equation Modeling (SEM) approach. The results of this study found that brand awareness, brand image and perceived quality can be significantly influenced by the authentication variable. Brand loyalty can be significantly influenced by brand awareness variables. Brand loyalty cannot be influenced by brand image variables and perceived quality. Brand choice intention can be significantly influenced by the brand loyalty variable.